Technology-Enhanced Bibliometric Analysis Of Didactic Transposition In Mathematics Education - Wicaksono, Agung; Suryadi, Didi; Fatimah, Siti; Suhendra, Suhendra; Warli, Dwi (Koordinat Jurnal MIPA, 2025)
This study analyzes the trend of didactic transposition research in mathematics education for the period 2014–2024 using a bibliometric approach with data from Scopus processed through VOSviewer and RStudio. Didactic transposition plays an important role in transforming scientific knowledge into materials that can be taught and understood by students, bridging the gap between academic theory and learning practice. The results of the analysis show an increase in publications in the past decade, with major journals such as Discrete Applied Mathematics, ZDM–Mathematics Education, and International Journal of Science Mathematics Education. China is the country with the largest research contribution in this field. In addition, bibliometric mapping identifies themes that are still rarely researched, such as Anthropology of Theory Didactic, algebra, cultural transposition, and calculus, which have the potential to be the focus of further research. This study provides insights for academics and education practitioners to understand the development of didactic transposition research and direct future research. By identifying research gaps that are minimally explored, the results of this study are expected to encourage the development of more effective teaching strategies, especially in mathematics learning, and strengthen the adaptation of didactic transposition-based curriculum